Empirical Studies in Translation: Methodological and Epistemological Questions - Neunzig, Wilhelm (TTR)

(untitled) (Association canadienne de traductologie, 2011)
When a qualitative leap forward is taken in any scientific discipline, the change is usually accompanied by an increased interest in research. This occurred in Translation Studies in the 1950s and in the 1990s. This paper outlines some of the most important epistemological and methodological questions faced by researchers who want to apply the so called “scientific method” to empirical research in translation. We will discuss the main steps in the research process: designing an experiment, selecting subjects or the object of study, defining experimental and control groups, controlling independent variables, choosing instruments that will measure what we want to measure and which will give us reliable data to analyse. The whole procedure should be intelligible and transparent, the objectives relevant and the results clear.